Effectiveness of an Instructional Program for Nurses' About Nursing Documentation at Pediatric Surgical Wards - Huda A. Ibraheam, Suad Hassoon Khudhair, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Evaluate the effectiveness of the instructional program for nurse's knowledge's about nursing documentation at pediatric surgical wards. Study design: A quasi-experimental design was implemented in the research to achieve the study goals by using pre- and post-tests for one group of nurses in pediatric surgical wards. in Baghdad city. The study has been carried out during the period extended from the 23th december 2021 to 20th July 2022. Data collection: It was done at three times: baseline data (before any instruction was provided to the study group), then post-test 1 after 21 days of starting to give the instructional program (in the study group), and post-test 2 after 2 months of starting to give the instructional program. Conclusion: Illustrated from this study, the nurses have poor knowledge regarding nursing documentation at pediatric surgical wards at pretest in study group. Association between nurses' knowledge and their (gender, level of education, years of experience and main source of information. Recommendations: Recommendations were made based on findings. for further research is imperative, that will pay more attention to the accuracy of nursing documentation, factors leading to variation in practice, flaws in nursing documentation quality and the effects of these on nursing practice and pediatric patient outcomes.